Management of Strengthening Cultural Values Achieving in Improving the Quality of Learning - Fajar Cahyono; Sutaryat Trisnamansyah; Iim Wasliman; Supyan Sauri (Journal of Islamicate Studies, 2020)
Intercultural competence is a basic part of development in realizing a form of sustainable development. The world of education is the part that builds the unit in which culture is built in it with careful alignment and balance of development, appropriate changes and accurate implementation, making the value of valuable quality achievements to become the basis of the culture that will be built and developed. Potential theory is part of the development of the value of Achieving Culture. The aim of the research itself is to find a picture related to the Management of Strengthening Achieving Cultural Values in Improving the Quality of Learning. Research Questions Focus on: 1) Accuracy; 2) Accuracy; 3) Accuracy of Management to Strengthen Achieving Cultural Values in Improving the Quality of Learning. Qualitative research methods are applied in connection with the research itself as part of a research instrument that is built through the process of documentation, observation and interviews. The results show that 1) Accuracy in building Management Achieving Cultural Values Strengthening in Improving the Quality of Learning has not been able to fully answer the challenges of development that are currently running and developing: 2) Accuracy in Management Strengthening Achievement Cultural Values in Improving the Quality of Learning in building and optimizing potential there is not identified fundamentally; 3) Management Accuracy Strengthening Achieving Cultural Values in Improving the Quality of Learning in its implementation is limited to a limited basis of understanding and is not built fundamentally on the basis of the principles of learning and education which are rooted in building intercultural competence in building knowledge into knowledge.